2021
DOI: 10.31580/jrp.v3i1.1958
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Marital Satisfaction in Individualistic and Collectivist Cultures: A Mini Review

Abstract: This article highlights key empirical and conceptual progress in understanding of predictors of marital satisfaction. The article brings together studies in this area summarizing the key findings, and then focuses on comparison of marital satisfaction predictors across individualistic and collectivist cultures. The researches on marital relationships currently addresses the concepts like satisfaction, marital success, consensus, companionship, adjustment, quality or some concepts relevant to satisfaction of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Após a intervenção os casais desenvolveram habilidades de comunicação construtiva, de afeto e resolução de problemas, o que impactou na satisfação conjugal (Durães et al, 2020;Kazim & Rafique, 2021;Wagner et al, 2019). Os resultados deste estudo concordam com outros trabalhos em terapia de casais (Doss et al, 2022;Durães et al, 2020;Fentz & Trillingsgaard, 2016), demonstrando que a melhoria da comunicação, afeto e resolução de problemas reduzem conflitos, melhorando a qualidade do relacionamento conjugal, bem como a satisfação.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Após a intervenção os casais desenvolveram habilidades de comunicação construtiva, de afeto e resolução de problemas, o que impactou na satisfação conjugal (Durães et al, 2020;Kazim & Rafique, 2021;Wagner et al, 2019). Os resultados deste estudo concordam com outros trabalhos em terapia de casais (Doss et al, 2022;Durães et al, 2020;Fentz & Trillingsgaard, 2016), demonstrando que a melhoria da comunicação, afeto e resolução de problemas reduzem conflitos, melhorando a qualidade do relacionamento conjugal, bem como a satisfação.…”
Section: Discussionunclassified
“…São múltiplos os fatores que podem interferir na conjugalidade e na satisfação conjugal, incluindo variáveis sociodemográficas (Durães et al, 2020;Rady et al, 2021), vida financeira (Wagner et al, 2019), parentalidade (Bolsoni-Silva & Loureiro, 2020a;Hosokawa & Katsura, 2017), comportamentos infantis (Bolsoni-Silva & Loureiro, 2020a;Mark & Pike, 2017) e saúde mental (Choi & Jung, 2021;Hsiao, 2017). Há evidências quanto à qualidade da comunicação positiva, da baixa ocorrência de comunicação negativa, do afeto positivo e de estratégias de resolução de problemas para a qualidade e satisfação conjugal (Bolsoni-Silva & Loureiro, 2020a;Kazim & Rafique, 2021). Apresentam-se algumas investigações que exemplificam tais relações.…”
unclassified
“…Another study has found that positive and negative behaviors, shared activities and companionship predict marital satisfaction (Kazim & Rafique, 2021). In a sample of 365 couples, Mirhosseini et al (2020) study determined that marital satisfaction is predicted by the wife's age, education, and occupation.…”
Section: Marital Satisfactionmentioning
confidence: 99%
“…We must understand love; we must be able to teach it, create it, and predict it, …." (p. 181) to Kazim and Rafique (2021) that lists romantic love as a predictor of marital satisfaction that spans across cultures. A Pew Research survey (Cohn, 2013) supported the importance of romantic love as the foremost reason why Americans marry (93% -for married responders/84% -for unmarried responders) with more traditional reasons trailing behind, such as making a lifelong commitment (87/74), companionship (81/63), having children (59/44), and financial stability (31/30); the importance of love in determining a marriage partner was confirmed in other research as well (Huston, 2009;Simpson et al, 1986;Sprecher & Hatfield, 2017).…”
Section: Introductionmentioning
confidence: 99%